Strength in power sports: the latest scientific results - Marques, M. C. (Journal of Physical Education and Sport, 2011)
Problem Statement: During the last decades, strength and power training has been a major issue for, coaches, athletes and researchers. Unfortunately, despite the increasing professionalization of coaches and athletes, there is little research data concerning performance in elite athletes. Several studies showed that a specific strength training program can improve athletes` maximal force and power production, reduce the incidence of injury, and contribute to faster injury recovery times, thereby minimizing the number of missed practice sessions and competitions. To our best knowledge, however, there is no apparent consensus on the appropriate method of strength and muscular power training to enhance performance, especially in typically power sports. On this, some questions remain unresolved and there have focused objective of our study: How much strength does an athlete need? Is the maximum strength the key for success? Is the muscular power the main issue? Approach: Therefore, the aim of this study focuses on a literature scientific search extended about strength in power sports specifically. Results: Studies in this area continue to contradict because they differ markedly in terms of design factors, including mode, frequency, intensity, frequency of training, and training history of subjects. Conclusions/Recommendations: We can conclude that once a given level of strength training intensity has been reached in trained athletes, the appropriate physiological adaptations may well be optimized and that training beyond this limit provides no further benefits